The role of FET-PET in patient selection and response assessment for reirradiation in recurrent glioblastoma - Zarębska, Izabela; Blok, Maciej; Marjański, Michał; Harat, Maciej (Frontiers in Oncology, 2025)
Radiation treatment with modern techniques is frequently used in the complex interdisciplinary management of glioblastoma, both in primary and recurrent setting. However, standard imaging limits the ability to precisely distinguish treatment-related changes from tumor progression and to accurately assess the outcomes of radiotherapy. Given the challenges, there is growing need for advanced imaging modalities that can enhance diagnostic precision and guide therapeutic decision. One such modality is FET-PET, whose role in glioblastoma radiotherapy is increasingly recognized - from target definition to response assessment and differentiation between progression and post-irradiation changes. Recently, PET RANO criteria have been published, providing an optimal strategy for evaluating treatment response using amino-acid PET. Earlier, contributions from the PET/RANO group also supported the integration of PET imaging in radiotherapy planning and monitoring of glioma patients. Increasing evidence highlights the advantages of amino-acid PET over standard RANO MRI in predicting overall survival. However, its value in case of patient selection and monitoring of reirradiation is less clear. In this narrative review, we aimed to summarize the published data on FET-PET in patients after initial treatment from the perspective of radiation oncologist. We focused on the role of FET-PET in accurate diagnosis of recurrence and in treatment response after reirradiation.